Factors associated with anemia in hospitalized pregnants of the San José Hospital - Soto Ramirez, Jesús (2020)
Objective: To identify the factors associated with anemia in pregnant women hospitalized in the gynecology and obstetrics service of the "San José" Callao-Lima hospital. Material and methods: observational, analytical, cross-sectional study with retrospective data collection.  Results: we found a prevalence of 78.9% of anemia in pregnant women. Pregnant women in the 1st trimester had a higher percentage of anemia (38.6%) (p = 0.00); 54.6% of pregnant women under 30 years old had anemia (p = 0.01), the odds for age was 2.2; Pregnant women with a BMI of 25 to 29.9 were the ones with the highest percentage of anemia (36.3%) (p = 0.29); The multiparous pregnant women were the ones that presented greater anemia (61.7%) (p = 0.03), the odds for parity was 1.83; pregnant women without NPC had a higher percentage of anemia (64.9%) (p = 0.00), the calculated odds were 0.03; pregnant women who did NOT present preeclampsia and eclampsia obtained a higher percentage of anemia, 59.1% and 71.4% respectively. The pregnant women who did present an intergenetic period are the ones with the greatest anemia (56.3%) (p = 0.00), the calculated odds were 5.52 (95% CI (3.16 - 9.65)). Conclusions: The factors that were significantly associated with anemia were maternal age, gestational age, parity, prenatal controls and the intergenetic period. In contrast, factors that were not significantly associated were pre-eclampsia, eclampsia, and body mass index.